IDENTIFIKASI KESULITAN PEMAHAMAN SISWA PADA MATERI USAHA DAN ENERGI - Hikmah, Dwi Lailatul; Putri, Aisyah; Setiaji, Bayu (PT. Media Akademik Publisher, 2024)
This study aims to find out how misconceptions experienced by high school students on work and energy material. The method used is a mixed-research method. Data collection was carried out on 288 science students of grade XI at State Senior High School 8 in the City of Jambi using instruments in the form of four-tier diagnostic tests and interviews. The results showed that the average misconceptions experienced by students in the work and energy materials are classified in the low category because the average percentage obtained is 24%. The sub-concept sequences identified were the misconceptions of which had the highest percentage, namely: effort and potential energy (80%); the relationship between kinetic energy, potential energy, and mechanical energy (43%); and positive and negative efforts (23%).